The Effect of Cadre Training on the Knowledge and Skills of Integrated Healthcare Center Cadres in Monitoring the Growth of Toddlers - Jamilah, Jamilah; Toaha, Aminah; Novaria, Astri Ayu; Wahyutri, Endah (Journal of Health and Nutrition Research, 2023)
Stunting is still a global health emergency, and this is a burden for developing countries including Indonesia. Based on the report, Indonesia is the country with the 5th largest contributor to stunting worldwide. The empowerment of cadres is considered very helpful in monitoring children's growth and development. This study aims to determine the training of cadres on knowledge and skills in monitoring the growth of toddlers in the working area of the Samarinda City Health Centre. The research is a quasi-experimental design conducted in July – August 2023 in the working area of the Samarinda City Health Center, East Kalimantan, Indonesia. A total of 66 cadres were involved as respondents by setting inclusion and exclusion criteria. The data was then collected and analyzed with the Wilcoxon and Mann-Whitney tests. Results show that there is an effect of training using modules on cadre knowledge (p = 0.000), there is an effect of training using videos on cadre knowledge (p = 0.000), there is an effect of training using modules on cadre skills (p = 0.000), and there is an effect of training using videos on cadre skills (p = 0.000). There is a difference. These results show that module media is more effectively used in training than video. Both forms of training exert the same effect. However, module-based training is more effective than video, this is because module media builds interaction among cadres